2018
DOI: 10.1093/mnras/sty3062
|View full text |Cite
|
Sign up to set email alerts
|

uGMRT detections of H i 21-cm absorption associated with intermediate redshift galaxies

Abstract: I report detections of four new Hi 21-cm absorbers associated with sources at intermediate redshifts, 0.7 < z < 1.0. The sources are part of a sample of 11 radio-loud galaxies, all at 0.7 < z < 1.0, that were searched for associated Hi 21-cm absorption using uGMRT. Previously, just four such absorbers were known in the literature at these redshifts; the current observations have increased the total to eight. The results indicate that the detection fraction at intermediate redshifts could be as high as that at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Besides re-detecting Hi absorption in 6 known systems, they surprisingly did not detect any new system in the spectra of 108 sources free from RFI, and none beyond a redshift of 0.7. In contrast, for a sample of 11 compact (mostly CSS/PS) sources in the intermediate redshift range 0.7 < z < 1, 4 were detected in Hi absorption using the uGMRT by Aditya (2019).…”
Section: Atomic Gasmentioning
confidence: 87%
See 1 more Smart Citation
“…Besides re-detecting Hi absorption in 6 known systems, they surprisingly did not detect any new system in the spectra of 108 sources free from RFI, and none beyond a redshift of 0.7. In contrast, for a sample of 11 compact (mostly CSS/PS) sources in the intermediate redshift range 0.7 < z < 1, 4 were detected in Hi absorption using the uGMRT by Aditya (2019).…”
Section: Atomic Gasmentioning
confidence: 87%
“…In this scenario, activity lasts ∼ 10 3 -10 4 yr and episodes are separated by ∼ 10 4 -10 6 yr (Czerny et al, 2009;Wu, 2009a;Siemiginowska et al, 2010). Jet disruption is another way of producing short-lived radio sources (e.g., De Young, 1991;Higgins et al, 1999;Wang et al, 2000;Wiita, 2004;Sutherland and Bicknell, 2007;Wagner and Bicknell, 2011;Mukherjee et al, 2016Mukherjee et al, , 2017Mukherjee et al, , 2018bBicknell et al, 2018;Aditya, 2019). If the jets in some sources disrupt (and the source fades quickly) before the radio source propagates out of the core, the distribution of number vs source size (O'Dea and ) can be reproduced (Alexander, 2000;Kaiser and Best, 2007;An and Baan, 2012).…”
Section: Transient or Episodic Sourcesmentioning
confidence: 99%
“…While this has been well studied in the nearby Universe, it is crucial to extend these studies to higher redshifts when feedback processes have the most impact (Hopkins & Beacom 2006). Recent studies searching for neutral gas outflows at z ∼ 1 have also shown evidence for fast outflows, although the sample size is still relatively small (Aditya & Kanekar 2018a;Aditya 2019). While FLASH will not be sensitive to the low optical depths typically observed in fast outflows for the majority of sources, it will provide a sample of powerful radio galaxies with large gas reservoirs which can be targeted with deeper observations using, for example, MeerKAT.…”
Section: Feedback and Triggeringmentioning
confidence: 99%
“…In the redshift range 0.42 < 1.0 there are a few previous studies (e.g. Aditya & Kanekar 2018b;Aditya 2019;Murthy et al 2022), but we chose to us our own data to minimize any selection bias. As noted above, the detection rate here is 2.9 +9.7 −2.6 %.…”
Section: Comparison With Other Surveys At Different Redshiftsmentioning
confidence: 99%